Реалізація швидкого перетворення Фур'є на ПЛІС - Васильєв, О. Ю. (ХНУРЕ, 2024)
This work focuses on researching and implementing a real-time Fast Fouri er Transform (FFT) application using a pipelined approach on modern Field Programmable Gate Arrays (FPGA). The author provides theoretical foundation and proposes a methodology for selecting solutions with optimal resource efficiency. Following this methodology, the FFT application is designed, verified, and implemented on Xilinx FPGA. The choice of Xilinx FPGA adds practical validation to the proposed methodology. These inquiries offer avenues for fur ther understanding the research and its implications.
Keywords: ПЛІС; перетворення Фур'є